Electricity cross-subsidies in the People's Republic of China: Equity, reverse Ramsey pricing, and welfare analysis - Yumin Li; Yan Jiang; Changgui Dong (Asian Development Bank Institute (ADBI), 2020)
The Chinese government has implemented reverse Ramsey pricing in the People's Republic of China's (PRC) electricity market, i.e., the residential electricity price has been lower than the industrial electricity price for decades, and the claimed rationale for this reverse Ramsey pricing is equity (i.e., low residential prices ensure that low-income households enjoy basic living conditions). Many have argued that the PRC's government should have adopted Ramsey pricing in the electricity industry to achieve efficient outcomes, which implies that the residential electricity price should be higher than the industrial electricity price based on their price elasticities. This paper presents one explanation of the phenomenon of reverse Ramsey pricing in the Chinese power market. In this paper, based on a modified Ramsey model, we assume the government has different weights on residential and industrial consumer surplus and derive a reverse Ramsey pricing rule. To numerically demonstrate that the reverse Ramsey pricing rule is reasonable under some circumstances, we calibrate the model and simulate social welfare under different scenarios. We find that the reverse Ramsey pricing rule is optimal if we introduce equity considerations, and the greater the weight of the residential sector, the lower the residential electricity prices. Our social welfare simulation results under different scenarios provide useful guidance for policy makers in future energy reform.
Keywords: Q41; Q48; 330; multi-objective regulation; reverse Ramsey pricing; social welfare